Orthopaedic Aspects of Marfan Syndrome: The Experience of a Referral Center for Diagnosis of Rare Diseases. (5th December 2016) - De Maio, Fernando; Fichera, Alessandro; De Luna, Vincenzo; Mancini, Federico; Caterini, Roberto
Abstract : Marfan syndrome is caused by mutations in the fibrillin-1 gene ( FBN1 ). The most important features affect the cardiovascular system, eyes, and skeleton. The aim of this study was to report the most frequent musculoskeletal alterations observed in 146 patients affected by Marfan syndrome. Fifty-four patients (37%) underwent cardiac surgery and 11 of them received emergent surgery for acute aortic dissection. Ectopia lentis was found in 68 patients (47%) whereas myopia above 3D occurred in 46 patients (32%). Musculoskeletal anomalies were observed in all patients with Marfan syndrome. In 88 patients (60.2%), the associated "wrist and thumb sign" was present; in 58 patients (39.7%), pectus carinatum deformity; in 44 patients (30.1%), pectus excavatum; in 49 patients (33.5%), severe flatfoot; in 31 patients (21.2%), hindfoot deformity; in 54 patients (36.9%), reduced US/LS ratio or increased arm span-height ratio; in 37 patients (25.3%), scoliosis or thoracolumbar kyphosis; in 22 patients (15%), reduced elbow extension (170° or less). Acetabular protrusion was ascertained on radiographs in 27 patients (18.4%). Orthopaedic aspects of the disease are very important for an early diagnosis; however, we have not observed definite correlations between the extent of orthopaedic involvement and aortic complications.